RNA-binding proteins as a point of convergence of the PI3K and p38 MAPK pathways - Ram KC eVenigalla; Martin eTurner (Frontiers in Immunology, 2012)
Understanding the mechanisms by which signal transduction pathways mediate changes in RNA abundance requires the examination of the fate of RNA from its transcription to its degradation. Evidence suggests that RNA abundance is partly regulated by posttranscriptional mechanisms affecting RNA decay and this in turn is modulated by some of the same signalling pathways that control transcription. Furthermore, the translation of mRNA is a key regulatory step that is influenced by signal transduction. These processes are regulated, in part, by RNA-Binding Proteins (RBPs) which bind to sequence specific RNA elements. The function of RBPs is controlled and co-ordinated by phosphorylation. Based on the current literature we hypothesize that RBPs may be a point of convergence for the activity of different kinases such as PI3K and MAPK which regulate RBP localisation and function.